Prediction and Analysis of Borosilicate Glass Surface Deformation Induced by Flame Jet - Biling Wang; Yutang Zhai; Xinming Zhang; Xinxin Qi; Weijie Fu (Machines)
To address the issues of low processing efficiency, poor forming accuracy, and internal damage in glass material processing, this study proposes the use of flame jet forming. However, the mechanism of flame jet processing requires further elucidation. This research investigates the relationship between the indentation morphology on the glass surface and the inlet velocity of the flame jet. A theoretical model was established through mathematical analysis to reflect this relationship. The model’s accuracy was validated using numerical simulation methods. By comparing experimental data with theoretical model results, surface tension was incorporated, and the model was iteratively optimized using MATLAB R2024a. The final optimized model demonstrated an absolute error range of 0.009 to 0.069 mm. This study confirms the feasibility of flame jet processing and enriches the understanding of its mechanism, providing a novel, efficient, and precise method for processing glass materials.